MARKETING OF NON-TIMBER FOREST PRODUCTS IN THREE HAMLETS OF THE DISTRICT OF JOSE CRESPO Y CASTILLO, HUANUCO - TICLLACURI-MALLQUI, Amanda (2023)
Non‑timber Forest Products (PFNM) are wild products found in the forest that are gaining importance due to the different uses they provide to man and his environment. This exploratory study aims to publicize the NTFPs that trade in 3 hamlets in the district of Jose Crespo y Castillo, province of Leoncio Prado, Huanuco region in Peru. The primary data was collected through a semi‑structured interviews with 13 farmers from the Angashacu, Bajo Cotomono and La Victoria. They were chosen randomly. The results show aguaje, cat's claw and sangre de grado as the most collected products. The sale of NTFPs, mainly aguaje, can generate more income than the sale of agricultural products for these residents, despite the fact that their use isonly for a few months.